ECONOMIC ANALYSIS OF INTERCROPPING OKRA WITH LEGUMES IN OKRA/LEGUME BASED INTERCROP - Ajayi, Oluwakayode Emmanuel; Adeoye, Iyabo B; Shittu, Olanrewaju A (Journal of Agricultural Sciences (Belgrade), 2017)
A field study was carried out in vegetable research field of National Horticultural Research Institute, Ibadan, Nigeria during the late raining season of 2015 to determine appropriate okra/legume-based cropping system that will increase crop yield and farmer’s income. The experiment was arranged in a randomized Complete Block Design (RCBD) with three (3) replicates, the treatments comprised intercropping Okra with groundnut or cowpea planted at varying spacing (60cm x 30cm, 60cm x 40cm, 60cm x 50cm and 60cm x 60cm). Okra was planted at a spacing of 60cm x 40cm on a plot size of 3 m x 2.4 m (7.4 m2). Data collected was subjected to analysis of variance (ANOVA) and significant means were separated using the least significant difference (LSD) test at 5% probability level. Economic analysis of the cropping mixture was carried out using gross margin analysis, Monetary Advantage Index and Benefit to Cost ratio analysis. Result revealed that LER of 1.62 was recorded in okra/groundnut at 60 cm x 40 cm and 1.74 in okra/cowpea at 60 cm x 30 cm. Okra/Cowpea spaced at 60 cm x 30 cm was the most remunerative (₦859,192/ha), followed by Okra/Cowpea spaced at 60 cm x 50 cm (₦744,212/ha) while Okra/Cowpea spaced at 60 cm x 60 cm was the least remunerative. Highest gross margin of ₦2,188,961/ha was obtained in Okra/Groundnut spaced at 60 cm x 40 cm. The least return was obtained in Okra/Groundnut spaced at 60cm x 60cm (₦700,103/ha). The economic analysis revealed that Okra/Cowpea spaced at 60cm x 30cm produced the highest gross margin and Monetary Advantage Index of ₦859,192/ha and ₦450,447/ha while Okra/Groundnut spaced at 60cm x 40cm gave the highest gross margin of ₦2,188,961/ha and Monetary Advantage Index of ₦924,642/ha.